A functional evaluation of feeding in the surgeonfish Ctenochaetus striatus: the role of soft tissues. Issue 1 (31st January 2018) - Tebbett, Sterling B.; Goatley, Christopher H. R.; Huertas, Víctor; Mihalitsis, Michalis; Bellwood, David R.
Abstract : Ctenochaetus striatus is one of the most abundant surgeonfishes on Indo-Pacific coral reefs, yet the functional role and feeding ecology of this species remain unclear. This species is reported to possess a rigid structure in its palate that is used for scraping, but some authors have reported that this element is comprised of soft tissue. To resolve the nature and role of this structure in the feeding ecology of C. striatus we examined evidence from anatomical observations, scanning electron microscopy, histology, X-ray micro-computed tomography scanning, high-speed video and field observations. We found that C. striatus from the Great Barrier Reef possess a retention plate (RP) on their palates immediately posterior to the premaxillary teeth which is soft, covered in a thin veneer of keratin with a papillate surface. This RP appears to be used during feeding, but does not appear to be responsible for the removal of material, which is achieved primarily by a fast closure of the lower jaw. We infer that the RP acts primarily as a 'dustpan', in a 'dustpan and brush' feeding mechanism, to facilitate the collection of particulate material from algal turfs.